From GERM (Global Educational Reform Movement) to NERM (Neoliberal Educational Reform Madness) - Yoon, Ee-Seul (Critical Education, 2024)
This article examines a popularized term, the Global Education Reform Movement (GERM), and its underlying paradigm of neoliberalism. It elucidates neoliberalism’s maddening effects on the education sector, especially public education. To analyze these effects, I draw from and adapt Michel Foucault’s analytical approach to madness. My analysis focuses on the following maddening effects of neoliberalism on education: (1) it obstructs us from seeing inequalities; (2) it creates a desperate passion amid the rise of school choice; and (3) it eliminates reason and creates unreason in the school selection and admissions processes. My analysis is based on reflections on my decade-long research on school marketization and school choice in Canada. I conclude by suggesting that collective visions and concrete steps are needed to move toward equitable educational structures, discourses, and practices that resist or challenge the neoliberal education reform madness (NERM).